A Pengembangan Media Poster Berbasis Pendidikan Karakter pada Topik Keberagaman Kebudayaan di Indonesia untuk Meningkatkan Hasil Belajar IPS Kelas V SD Negeri Kintelan 2 Yogyakarta - Jahrudin, Putri Alwiyah; Zulfiati, Heri Maria; Wardani, Kristi (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2023)
The purposes of this study were to : 1) describe the development of education’s character based on poster media according to what students and fifth grade teachers needed in Kintelan 2 Yogyakarta Elementary school; 2) describe the validity level of education’s character based on poster media to increase the knowledge of students learning outcomes in cognitive aspect and concept understanding in Kintelan 2 Yogyakarta Elementary School; 3) to analyze the effectiveness of education’s character based on poster media to increase the knowledge of students learning outcomes in cognitive aspect and concept understanding in Kintelan 2 Yogyakarta Elementary School; 4) to identify the effectiveness of poster media to make disciplinary character, responsibility, curiosity, and cooperation of students in Kintelan 2 Yogyakarta Elementary School. The results of this research indicate that poster media based on character education is very suitable for use in improving social studies learning outcomes for Class V at SD Negeri Kintelan 2 Yogyakarta. This is shown in the results of material expert validation with a score of 90.91%. Meanwhile, the validation results from media experts were 94.64%. Poster media based on character education can improve learning outcomes in the cognitive aspect (knowledge). This increase can be seen from the results of the students' pre-test and post-test. The average increase in social studies learning outcomes for Class V at SD Negeri Kintelan 2 Yogyakarta was 40.9 with a percentage of 84.31%. Thus, poster media based on character education on the topic of cultural diversity in Indonesia can improve social studies learning outcomes for Class V at SD Negeri Kintelan 2 Yogyakarta.